RITUAL KASAMPU BAGI PEREMPUAN DI KECAMATAN KAMBOWA KABUPATEN BUTON UTARA: TAHAPAN PELAKSANAAN DAN MAKNA TUTURAN ADAT - Karoluslina; La Tike (Jurnal Bastra (Bahasa dan Sastra), 2026)
This study aims to describe and analyze the stages of the kasampu ritual for women in Kambowa District, North Buton Regency. The research employed a qualitative approach, with data collected through participatory observation and in-depth interviews. Informants were determined using a snowball sampling technique, involving three key informants, namely the bisa (ritual guide), the imam, and parents who organized the kasampu ritual, supported by additional informants from the ritual participants. Data analysis was conducted using source triangulation to ensure data validity. The findings indicate that the kasampu ritual consists of three main stages: (1) the preparation stage, which includes family deliberation, committee formation, scheduling, and preparation of ritual equipment; (2) the implementation stage, which involves the seclusion process and a series of rituals such as kapoluku, kahombo, kabhansule, kalengka, and kawiwiki as a means of moral, spiritual, and ethical guidance for women; and (3) the final stage, marked by the kapolantono kakuba and kabadakino kabere ceremonies, symbolizing physical and spiritual purification as well as the formal recognition of participants as adult women. The kasampu ritual functions as a form of character education based on local cultural values and as an effort to preserve the traditions of the Kambowa community.